2013
DOI: 10.1016/j.anr.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Workplace Multiple Cardiovascular Disease Risks Reduction Program

Abstract: Dual collaboration between the industry and nursing schools could establish a cost-effective program to improve health behaviors and health status of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Our study is the first to apply a realist review methodology to explore how, [40,59,61,62,65,66,68,73,81,82,84] 8 (73%) [40,65,66,68,73,81,82,84] Opportunity -Social Support 15 [60,[64][65][66][67][68]…”
Section: Resultsmentioning
confidence: 99%
“…Our study is the first to apply a realist review methodology to explore how, [40,59,61,62,65,66,68,73,81,82,84] 8 (73%) [40,65,66,68,73,81,82,84] Opportunity -Social Support 15 [60,[64][65][66][67][68]…”
Section: Resultsmentioning
confidence: 99%
“…However, there were certain contexts in which interventions based on this mechanism observed more success. Specifically, four [67,71,84,103,104] out of eight interventions [59,63,67,71,80,84,103,104] in Asia reported that participants were more likely to quit smoking. Interventions that utilized capability in community based settings or in schools also had positive results with 71% (5/7) [40, 70,77,81,104] and 80% (4/5) [40, 73,82,84], respectively reporting long-term smoking cessation.…”
Section: Demi-regularity -Capabilitymentioning
confidence: 99%
“…However, there were certain contexts in which interventions based on this mechanism observed more success. Speci cally, four [67,71,84,103,104] out of eight interventions [59,63,67,71,80,84,103,104] in Asia reported that participants were more likely to quit smoking. Interventions that utilized capability in community based settings or in schools also had positive results with 71% (5/7) [40,70,77,81,104] and 80% (4/5) [40,73,82,84], respectively reporting long-term smoking cessation.…”
Section: Demi-regularity -Capabilitymentioning
confidence: 99%